Patterns of depressive symptoms among younger elderly (60–74 years old) and older elderly (≥75 years old) in Jamaica. (August 2019) - Gibson, Roger C.; James, Kenneth; Waldron, Norman K.; Abel, Wendel D.; Eldemire-Shearer, Denise; Mitchell-Fearon, Kathryn
ABSTRACT: Objectives: We sought to explore factors associated with depressive symptom severity among older persons (≥60 years of age) and to compare the depressive symptoms commonly experienced by older elderly (≥75 years) with those commonly experienced by younger elderly (<75 years). Design: Secondary analysis was conducted on data from a nationally representative survey. Setting: Four parishes in Jamaica. Participants: A total of 2, 943 older community dwellers participated. Measurements: The survey included the Zung Self-rating Depression Scale (ZSDS), the Mini Mental State Examination (MMSE), and items on age, sex, and educational level. Linear regression analysis was used to determine the association between ZSDS score and: age, sex, MMSE score, and educational level. Logistic regression analysis was used to determine, for each ZSDS item, whether particular responses were more associated with older or younger elderly. Results: Higher ZSDS scores were associated with increasing age (B = 0.13, p < 0.001), lower MMSE score (B = −0.42, p < 0.001), the female sex (B = 3.52, p < 0.001), and lower educational level (B = −1.27, p < 0.001). The ZSDS items that were endorsed significantly more ( p < 0.05) by older elderly related to negative evaluations about their functionality and value. Hopelessness was also more prominent among the older elderly. The items that were endorsed significantly more ( p < 0.05) by the younger elderly had less of a focus. Conclusion: Among older persons, increasing age was associated with marginally higher levels of depressive symptoms. Female gender, cognitive deficits, preoccupations about value and functionality, and feelings of hopelessness may serve as useful screening parameters.